2023
DOI: 10.3390/foods12183509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sequential Inoculation of Tetragenococcus halophilus and Wickerhamomyces anomalus on the Flavour Formation of Early-Stage Moromi Fermented at a Lower Temperature

Xinzhi Li,
Xinyu Xu,
Changzheng Wu
et al.

Abstract: Microbial inoculation in moromi fermentation has a great influence on the physicochemical and flavour properties of soy sauces. This work investigated the effect of inoculating Tetragenococcus halophilus and Wickerhamomyces anomalus on the flavour formation of early-stage moromi (30 days) fermented at a lower temperature (22 °C) by determining their physicochemical and aroma changes. The results showed that single yeast or LAB inoculation increased the production of amino nitrogen, lactic acid and acetic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Li et al explored the impact of microbial inoculation with Tetragenococcus halophilus and Wickerhamomyces anomalus on the physicochemical and flavor properties of soy sauce during early-stage moromi fermentation at 22 • C. Their results indicated that single yeast or LAB inoculation enhances amino nitrogen, lactic acid, acetic acid, free amino acid, and key flavor component production levels. The sequential inoculation of T. halophilus and W. anomalus yielded higher levels of free amino acids and aromatic compounds, potentially due to synergistic effects, resulting in characteristic soy sauce flavor compounds and improved savory, roasted, and caramel intensities, suggesting a promising approach for high-quality moromi production at lower temperatures [40].…”
mentioning
confidence: 99%
“…Li et al explored the impact of microbial inoculation with Tetragenococcus halophilus and Wickerhamomyces anomalus on the physicochemical and flavor properties of soy sauce during early-stage moromi fermentation at 22 • C. Their results indicated that single yeast or LAB inoculation enhances amino nitrogen, lactic acid, acetic acid, free amino acid, and key flavor component production levels. The sequential inoculation of T. halophilus and W. anomalus yielded higher levels of free amino acids and aromatic compounds, potentially due to synergistic effects, resulting in characteristic soy sauce flavor compounds and improved savory, roasted, and caramel intensities, suggesting a promising approach for high-quality moromi production at lower temperatures [40].…”
mentioning
confidence: 99%